Evolutionary History of the Root Vole (Microtus oeconomus) as Revealed by Y Chromosome and Mitochondrial DNA sequences - Brunhoff, Cecilia (Cecilia Brunhoff, Dept. of Cell and Organism Biology, Lund University, Sweden, 2003)
The root vole ( Microtus oeconomus ) is a rodent with Holarctic distribution. In fact, it is the only Microtus vole found in both Eurasia and North America. Phylogeographic analyses of the root vole from across its distribution range were performed using mitochondrial and Y chromosome DNA sequences. Mitochondrial cytochrome b gene data demonstrate that the root vole is divided into four geographically distinct and well supported mtDNA phylogroups. Concordance between phylogeographic patterns in the root vole and other species suggest similarities in these species' responses to large-scale climatic change. The result of Y chromosome sequence analyses in the root vole is congruent with mtDNA, but the low sequence variability of the Y chromosome result in a phylogeographic pattern with much lower resolution. Differences between the mtDNA and Y chromosome phylogeographic patterns cannot be explained by differences in mutation rate alone, but is also affected by different evolutionary conditions and processes such as sex-biased dispersal, differences in male and female effective population sizes and local selective sweeps. Both mtDNA and Y chromosome data lend support for a subdivision of Fennoscandian root voles into two phylogroups with a complex history involving at least two colonization routes and, perhaps, glacial survival in northern Norway. These results contradict theoretical models that suggest low genetic diversity in previously glaciated areas. Analyses of two genetic markers, mtDNA and Y chromosome sequences, in concert have provided a more detailed picture of the evolutionary history of the root vole as well as the evolution of the two genetic systems. In addition, a phylogenetic study of 25 Microtus species based on mtDNA shows that the root vole belongs to an Asian group of Microtus voles.